Impact of substrate resistivity on spiral inductors at mm-wave frequencies. (August 2022) - Nyssens, Lucas; Rack, Martin; Schwan, Christoph; Zhao, Zhixing; Lehmann, Steffen; Hermann, Tom; Allibert, Frederic; Aulnette, Cécile; Lederer, Dimitri; Raskin, Jean-Pierre
Highlights: Parasitic surface conduction of high-resistivity substrates degrades quality factor of inductors. RF inductors quality factor strongly improves with high-resistivity substrate. mm-wave inductors need re-design for large gain in quality factor with high-resistivity substrate. Abstract: The quality factor (Q) of two inductors for 5–60 GHz applications fabricated in an industrial back-end of line (22FDX® from GlobalFoundries) with thick Cu metal layers on top of several Si substrates of different bulk resistivities is analyzed in this paper. The low frequency RF inductor shows an improvement of up to 44% in Q with a high-resistivity substrate. However, no significant improvement is observed for the high-frequency MMW fabricated inductor. This is identified to be due to lower electric field concentration in the substrate due to the small geometry of this MMW inductor that is realized in the top metal Cu layer. Nevertheless, simulations show that a 30% improvement can be achieved with a low loss substrate when designing a MMW inductor as a stacked coil of all BEOL thick metal layers.